2019
DOI: 10.3233/jad-180403
|View full text |Cite
|
Sign up to set email alerts
|

Perception of Benefits and Risks of Neurocognitive Disorders Diagnosis: A French National Survey

Abstract: Background: Neurocognitive disorders (NCD) are underdiagnosed in primary care, mainly because of the misunderstanding of benefits associated with timely diagnosis. Objective: The aim of this study was to explore the benefits and risks of diagnosis in a population of general practitioners (GPs), specialized physicians (SPs), other healthcare professionals (HPs), and informal caregivers (ICs). Methods: A questionnaire was submitted to GPs, SPs, HPs. and ICs. It aimed at evaluating benefits and risks related to N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…This study was a national multicenter descriptive survey conducted in France. A standardized selfadministrative questionnaire was sent by email in June 2016 and replies received up to the end of November 2016 were included, as previously described [9]. Participants were free to take part in the study, questionnaires were anonymous, and no incentive was given in exchange for participation to this study.…”
Section: Study Design and Settingmentioning
confidence: 99%
See 3 more Smart Citations
“…This study was a national multicenter descriptive survey conducted in France. A standardized selfadministrative questionnaire was sent by email in June 2016 and replies received up to the end of November 2016 were included, as previously described [9]. Participants were free to take part in the study, questionnaires were anonymous, and no incentive was given in exchange for participation to this study.…”
Section: Study Design and Settingmentioning
confidence: 99%
“…However, the first European joint action on Alzheimer 3 Disease (AD) recommended in 2013 a timely diagnosis that should be accessible to all sections of the community at a stage when people first notice changes in cognition or behavior, complain, or present with a situation at risk [2]. At the personal level, diagnosis of NCD is not experienced in terms such notions of time, and it has recently been reported that personalized diagnosis is more pertinent; the latter is defined as a diagnosis strategy in accordance with the dyad patient/caregiver's needs and wills respecting the general principle of autonomy and should lead up to a global and personalized care plan established together with the patient, his or her close caregiver, and all the professionals involved [9,10].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Personal benefits of early detection include opportunities to plan for the future, seek education and support, and address potential safety issues, such as the ability to drive and take medications as directed (Garnier-Crussard et al, 2019; Smith et al, 2017). Patients and families want to learn more about their symptoms and condition (Tochel et al, 2019).…”
Section: Introductionmentioning
confidence: 99%